Valeriana jatamansi Jones ex Roxb. Against Post-Traumatic Stress Disorder, Network Pharmacological Analysis, and In Vivo Evaluation - Yang, Xue; Guo, Jian-You; Jiang, Ya-Ni; Liu, Meng-Meng; Li, Qiu-Yu; Li, Jia-Yuan; Wei, Xiao-Jia; Wan, Guo-Hui; Shi, Jin-Li (Frontiers in Pharmacology, 2021)
Zhi zhu xiang (ZZX) is the root and rhizome of Valeriana jatamansi Jones ex Roxb. Recent studies have shown that ZZX can exert antianxiety, antidepressant, and sedative effects. Because post-traumatic stress disorder (PTSD) is similar to depression and anxiety in terms of its etiology, pathogenesis, and clinical manifestations, it is possible that ZZX may also be useful for the prevention and treatment of PTSD. In this study, a mouse model of PTSD was established and used to study the pharmacological action of a 95% ethanol extract of ZZX on PTSD via a series of classic behavioral tests. We found that a 95% ethanol extract of ZZX was indeed effective for relieving the symptoms of PTSD in mice. Moreover, network pharmacology analysis was used to predict the potential active ingredients, targets, and possible pathways of ZZX in the treatment of PTSD. The neurotransmitter system, the hypothalamic–pituitary–adrenal (HPA) axis, and the endocannabinoid (eCB) system were identified to be the most likely pathways for anti-PTSD action in ZZX. Due to the lack of a falsification mechanism in network pharmacology, in vivo tests were carried out in mice, and the expression levels of neurotransmitters, hormones, and genes of key targets were detected by enzyme-linked immunosorbent assay and real-time PCR to further verify this inference. Analysis showed that the levels of norepinephrine, 5-hydroxytryptamine, and glutamic acid were increased in the hippocampus, prefrontal cortex, and amygdala of PTSD mice, while the levels of dopamine and γ-aminobutyric acid were decreased in these brain regions; furthermore, ZZX could restore the expression of these factors, at least to a certain extent. The levels of adrenocorticotropic hormone, corticosterone, and corticotropin-releasing hormone were increased in these different brain regions and the serum of PTSD mice; these effects could be reversed by ZZX to a certain extent. The expression levels of cannabinoid receptor 1 and diacylglycerol lipase α mRNA were decreased in PTSD mice, while the levels of fatty acid amide hydrolase and monoacylglycerol lipase mRNA were increased; these effects were restored by ZZX to a certain extent. In conclusion, our findings suggest that ZZX may provide new therapeutic pathways for treating PTSD by the regulation of neurotransmitters, the HPA, and expression levels of eCB-related genes in the brain.